The Effectiveness of Pair Programming in Enhancing Elementary School Students’ Creative Thinking Skills in Coding Lessons - Febriarsita Eka Sasmita; Ummu Khairiyah; Pance Mariati (Universitas Negeri Surabaya, 2026)
This study aims to analyze the effectiveness of pair programming in coding lessons on enhancing elementary school students’ creative thinking skills. The research employed a quasi-experimental method with a nonequivalent control group design involving 44 elementary school students participating in a coding learning program. The subjects were divided into two groups: an experimental group learning through pair programming and a control group learning using the conventional direct instruction method. The research instrument used the Torrance Tests of Creative Thinking (TTCT) Figural A to measure three indicators of creative thinking: fluency, originality, and elaboration. Data analysis was conducted using paired sample t-tests and the Wilcoxon signed-rank test. The results showed a significant improvement in creative thinking skills in the experimental group compared to the control group, particularly in the fluency and originality indicators. However, the improvement in the elaboration indicator was not significant. These findings indicate that pair programming is an effective learning strategy to stimulate creative thinking in coding lessons at the elementary school level, especially in terms of idea fluency and originali.ty.